2010
DOI: 10.1089/hum.2009.189
|View full text |Cite
|
Sign up to set email alerts
|

Different Serum Enzyme Levels Are Required to Rescue the Various Systemic Features of the Mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPSs) are lysosomal storage disorders characterized by progressive accumulation of glycosaminoglycans (GAGs) in various tissues. Enzyme replacement therapy (ERT) for several MPSs is available to date. However, the efficacy of ERT is limited, in particular in compartments such as bone, cartilage, the brain, and the eyes. We selected a rodent model of an MPS, with no central nervous system storage, to study the impact, on systemic features of the disease, of various stable levels of exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 70 publications
10
57
1
Order By: Relevance
“…While the greatest improvements in height and endurance were seen primarily in patients with lower baseline uGAG levels ≤200 µg/mg creatinine, clinical parameters (such as walk distance in 6MWT and pulmonary function) in the high baseline uGAG group remained stable in the ERT group. However, additional or newer approaches may be required to increase the clinical benefit of galsulfase ERT in patients with rapidly progressive disease, such as different dosing schedules [Cotugno et al, 2010]) and/or substrate reduction therapy, both of which have not yet been tested in clinical studies [Schuchman et al, 2013; Simonaro et al, 2010; van Gelder et al, 2012]. Neonatal screening leading to early diagnosis and prompt ERT initiation may be key to improve the management and outcomes of patients with rapidly progressive disease [Furujo et al, 2011; Giugliani 2012; Horovitz et al, 2013; McGill et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…While the greatest improvements in height and endurance were seen primarily in patients with lower baseline uGAG levels ≤200 µg/mg creatinine, clinical parameters (such as walk distance in 6MWT and pulmonary function) in the high baseline uGAG group remained stable in the ERT group. However, additional or newer approaches may be required to increase the clinical benefit of galsulfase ERT in patients with rapidly progressive disease, such as different dosing schedules [Cotugno et al, 2010]) and/or substrate reduction therapy, both of which have not yet been tested in clinical studies [Schuchman et al, 2013; Simonaro et al, 2010; van Gelder et al, 2012]. Neonatal screening leading to early diagnosis and prompt ERT initiation may be key to improve the management and outcomes of patients with rapidly progressive disease [Furujo et al, 2011; Giugliani 2012; Horovitz et al, 2013; McGill et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Single systemic administration of AAV2/8 vectors encoding ARSB resulted in long-term production and systemic secretion of therapeutic ARSB from transduced hepatocytes (Cotugno et al, 2012). This resulted in amelioration of the MPS VI phenotype, including reduction of GAG storage and heart valve abnormalities and improvement of long bone length and mobility in both MPS VI rats and cats (Tessitore et al, 2008;Tessitore et al, 2009;Cotugno et al, 2010;Cotugno et al, 2011). These data bode well for clinical translation of AAV2/8-mediated liver gene therapy for MPS VI.…”
Section: Introductionmentioning
confidence: 77%
“…While in MPS VI rats close-to-normal levels of circulating ARSB are required to improve long bone length (Cotugno et al, 2010), in the feline model of MPS VI improvement of long bones can be achieved at lower levels of circulating ARSB obtained with low or intermediate doses of AAV2/8-TBG-fARSB. This could be explained by (1) the different vascularization of long bones or the different levels of mannose 6-phosphate receptor expression between the two species; and (2) the ARSB transgene type, in that we used the species-specific feline transgene in cats, whereas the human transgene was used in MPS VI rats (Cotugno et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,[61][62][63] Hemophilia A and B correction requires a relatively low continuous presence of normal protein in the circulation. Thus, Cantore et al 64 showed that liver-directed lentiviral vectormediated gene therapy of canine hemophilia B dogs provided stable, long-term FIX activity up to 1% of normal with therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%